Silicone rubber with high compression resistance and oxidation corrosion resistance and preparation method thereof

By forming a multi-branched cross-linked mesh structure in silicone rubber and using fiber fillers and white carbon black, the gas permeation and chemical corrosion problems of silicone tubes in high-pressure and high-temperature environments are solved, and the compressive and oxidative corrosion resistance is improved. Extends service life and improves safety.

CN119119742AActive Publication Date: 2024-12-13DONGGUAN ZHENGYUAN POLYMER MATERIAL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411370945.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-13
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

Existing silicone tubes are prone to gas penetration in high pressure, high temperature and hydrogen environments, and their performance decreases significantly after long-term contact with chemical substances. It is difficult to maintain flexibility and improve compression, oxidation and corrosion resistance, which affects service life and safety.

Method used

The reactant formed by dodecyl methacrylate and methyltriallyl silane is mixed and crosslinked with methylvinyl silicone rubber to form a multi-branched crosslinking network structure, and is combined with fiber filler and white Carbon black, assisted by catalyst, makes silicone rubber have better mechanical properties, oxidation and corrosion resistance and compressive resistance.

Benefits of technology

It significantly improves the compressive and oxidative corrosion resistance of silicone rubber, extends its service life and improves safety, and is suitable for hydrogen pipes in hydrogen-energy vehicles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005067555370000051
    Figure BDA0005067555370000051
  • Figure BDA0005067555370000061
    Figure BDA0005067555370000061
  • Figure BDA0005067555370000081
    Figure BDA0005067555370000081
Patent Text Reader

Abstract

The invention relates to silicone rubber with high compression resistance and oxidation corrosion resistance and a preparation method thereof. The silicone rubber composition is prepared from the following raw materials in parts by weight: 100 parts of methyl vinyl silicone rubber, 1 to 8 parts of active group double-terminated polydimethylsiloxane, 10 to 20 parts of 1, 1, 3, 3, 5, 5-hexamethyltrisiloxane, 1 to 5 parts of dodecafluoroheptyl methacrylate, 3 to 5 parts of methyl triallyl silane, 10 to 30 parts of white carbon black, 5 to 15 parts of fiber filler, 1 to 3 parts of catalyst A, 0.01 to 0.03 part of catalyst B and 0.001 to 0.003 part of inhibitor. A reactant formed by dodecafluoroheptyl methacrylate and methyltriallylsilane, active group double-terminated polydimethylsiloxane and 1, 1, 3, 3, 5, 5-hexamethyltrisiloxane are reacted with methyl vinyl silicone rubber to form a multi-branched chain cross-linked network structure, so that the anti-aging performance of the silicone rubber is improved, and the anti-aging performance of the silicone rubber is improved. Therefore, the obtained silicone rubber has better mechanical properties, oxidation corrosion resistance and compression resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of silicone rubber, and more specifically, to a high-pressure and oxidation-resistant silicone rubber and a preparation method thereof. Background Art

[0002] Silicone rubber has excellent softness, heat resistance, cold resistance, dielectric properties, ozone resistance and atmospheric aging resistance. It also has the advantages of environmental protection and non-toxicity. Therefore, it is often used in the production of various hoses, sealing gaskets, spacers, leather cups, valves, shockproof parts, etc.

[0003] Silicone tubes produced from silicone rubber are used in many fields due to their good elasticity, high stability, chemical corrosion resistance and softness. However, for silicone tubes used in automotive hydrogen fuel cells, the compression and oxidation corrosion resistance of silicone tubes become key challenges in high-pressure, highly chemically active environments such as hydrogen energy vehicles. Existing technologies mainly improve performance by increasing the thickness of the tube wall, but these methods often sacrifice flexibility or increase costs. There are also methods that produce silicone rubber braided tubes, form a multi-layer structure on the rubber tube wall, and weave with high-strength fibers to enhance the compressive pressure and mechanical properties of silicone tubes, but the production process is relatively cumbersome and the production efficiency is low.

[0004] At the same time, silicone tubes are prone to gas permeation in high pressure, high temperature and hydrogen environments, and their performance significantly decreases after long-term contact with chemicals, seriously affecting their service life and safety. Therefore, the development of a new silicone rubber material and its preparation method that can maintain the flexibility of silicone tubes and significantly improve their compression and oxidation corrosion resistance has become an urgent problem to be solved in the current hydrogen energy vehicle field. Summary of the invention

[0005] In order to obtain better flexibility and at the same time better pressure resistance and corrosion resistance, the present application provides a high pressure resistance and oxidation corrosion resistance silicone rubber and a preparation method thereof.

[0006] In a first aspect, the present application provides a high-pressure and oxidation-resistant silicone rubber, characterized in that it is composed of the following raw materials in parts by weight: 100 parts of methyl vinyl silicone rubber Active group double-terminated polydimethylsiloxane 1-8 parts 1,1,3,3,5,5-Hexamethyltrisiloxane 10-20 parts 1-5 parts of dodecafluoroheptyl methacrylate 3-5 parts of methyl triallylsilane 10-30 parts of white carbon black Fiber filler 5-15 parts Catalyst A1-3 parts Catalyst B 0.01-0.03 parts Inhibitor 0.001-0.003 parts.

[0007] In the above scheme, methyl vinyl silicone rubber has better flexibility, and the active group of dodecafluoroheptyl methacrylate is grafted with an active group of methyl triallyl silane, and the remaining two active groups react further with silicone rubber, and fluorine is introduced into the silicone rubber raw material system. The fluorine-containing polymer has better anti-oxidation and corrosion effect, and is combined with active group double-terminated polydimethylsiloxane and 1,1,3,3,5,5-hexamethyltrisiloxane with two active groups. After the reaction, a cross-linked network structure is formed, and the silicone rubber has better mechanical properties, anti-oxidation and corrosion properties, and compressive properties. When it is used to produce hydrogen pipes for hydrogen energy vehicles, it has better compressive properties.

[0008] Both fiber filler and silica play a reinforcing role, further improving the compressive and mechanical properties of silicone rubber.

[0009] In summary, the present application uses the reactants formed by dodecafluoroheptyl methacrylate and methyl triallylsilane, active group double-terminated polydimethylsiloxane and 1,1,3,3,5,5-hexamethyltrisiloxane to form a composite cross-linking reaction with methyl vinyl silicone rubber to form a multi-branched cross-linked network structure, and then combines fiber fillers and white carbon black with the assistance of a catalyst to make the obtained silicone rubber have better mechanical properties, antioxidant corrosion resistance and compressive resistance.

[0010] Preferably, the methyl vinyl silicone rubber is composed of the following raw materials in parts by weight: 20-40 parts of methyl vinyl silicone rubber with a vinyl content of 0.08-0.17% 30-40 parts of methyl vinyl silicone rubber with a vinyl content of 0.18-0.30% 20-50 parts of methyl vinyl silicone rubber with a vinyl content of 1.01-1.27.

[0011] The molecular formula of methyl vinyl silicone rubber is generally a straight chain type. When stretched, it is easy to deform and has poor resistance to low tear permanent deformation. By adding methyl vinyl silicone rubber with different vinyl contents, it is compounded to form a multi-branched polymer, and then further cross-linked with the graft formed by dodecafluoroheptyl methacrylate and methyl triallyl silane, active group double-terminated polydimethylsiloxane, and 1,1,3,3,5,5-hexamethyltrisiloxane to form a multi-branched cross-linked network structure, which further improves the mechanical properties, oxidation resistance and compressive resistance of silicone rubber.

[0012] Preferably, the number average molecular weight of the methyl vinyl silicone rubber is 100,000-500,000.

[0013] The methyl vinyl silicone rubber with the above number average molecular weight range is selected and reacted with the graft formed by dodecafluoroheptyl methacrylate and methyl triallylsilane, the active group double-terminated polydimethylsiloxane, and 1,1,3,3,5,5-hexamethyltrisiloxane to form a silicone rubber with better mechanical properties, antioxidant corrosion resistance and compressive resistance.

[0014] Preferably, the number average molecular weight of the active group double-terminated polydimethylsiloxane is 5000-8000.

[0015] The above molecular weight range allows the active group double-terminated polydimethylsiloxane to interact with the graft formed by dodecafluoroheptyl methacrylate and methyl triallylsilane, and 1,1,3,3,5,5-hexamethyltrisiloxane, and further cross-links the methyl vinyl silicone rubber to obtain a stable cross-linked network structure and obtain better mechanical, oxidation corrosion resistance and compression resistance. When used in automotive hydrogen fuel cell silicone tubes, it can further improve durability and safety of use.

[0016] Preferably, the active group double-terminated polydimethylsiloxane is one or more of hydroxyl double-terminated polydimethylsiloxane, aminopropyl double-terminated polydimethylsiloxane, and double-terminated methacryloxypropyl polydimethylsiloxane.

[0017] Hydroxyl double-terminated polydimethylsiloxane, aminopropyl double-terminated polydimethylsiloxane, and double-terminated methacryloxypropyl polydimethylsiloxane have double-terminated active groups and can be combined with the graft formed by dodecafluoroheptyl methacrylate and methyl triallylsilane and 1,1,3,3,5,5-hexamethyltrisiloxane to make the obtained silicone rubber have better mechanical properties, corrosion resistance and compressive resistance.

[0018] Preferably, the active group double-terminated polydimethylsiloxane is composed of hydroxyl double-terminated polydimethylsiloxane, aminopropyl double-terminated polydimethylsiloxane, and double-terminated methacryloxypropyl polydimethylsiloxane in a weight ratio of 1:(1.2-1.8):(1-3).

[0019] When hydroxyl double-terminated polydimethylsiloxane, aminopropyl double-terminated polydimethylsiloxane and double-terminated methacryloxypropyl polydimethylsiloxane are compounded, they play a synergistic role and interact with the grafted products formed by dodecafluoroheptyl methacrylate and methyltriallylsilane and 1,1,3,3,5,5-hexamethyltrisiloxane, making the performance of silicone rubber better.

[0020] Preferably, the fiber filler is polyetheretherketone fiber and / or aramid fiber.

[0021] Polyetheretherketone fiber and aramid fiber have good anti-oxidation and corrosion resistance, tensile strength, etc., and combined with the raw material system of the present application, the comprehensive performance of silicone rubber is further improved.

[0022] Preferably, the catalyst A is a platinum catalyst or a dipentadienyl vulcanizing agent.

[0023] The use of platinum catalyst and dipentadienyl vulcanizing agent can promote the formation of large molecular polymers in silicone rubber and facilitate the curing reaction, so that silicone rubber has better performance.

[0024] Preferably, the catalyst B is benzoyl peroxide; and the inhibitor is p-hydroxyanisole.

[0025] The use of catalyst B as a peroxide can promote the reaction of dodecafluoroheptyl methacrylate and methyl triallyl silane, and with the assistance of the inhibitor, the inhibitor inhibits the self-polymerization of the monomers, thereby forming a long-chain graft. When mixed with the silicone rubber raw material system, under the action of catalyst B, the active groups contained in the graft further react with methyl vinyl silicone rubber, and then cooperate with the active group double-terminated polydimethylsiloxane and 1,1,3,3,5,5-hexamethyltrisiloxane to form a network polymer of multi-crosslinked monomers, so that the obtained silicone rubber has better performance. In a second aspect, the present application provides a method for preparing a high-pressure-resistant and anti-oxidative-corrosion silicone rubber, comprising the following steps: Step 1: weigh dodecafluoroheptyl methacrylate, methyl triallylsilane, inhibitor, and catalyst B in parts by weight, mix them evenly, and heat them for reaction to obtain reactant C; mix active group double-terminated polydimethylsiloxane, 1,1,3,3,5,5-hexamethyltrisiloxane, white carbon black, and fiber filler in parts by weight to obtain mixture D; Step 2: Weigh methyl vinyl silicone rubber in parts by weight, and evenly mix all reactants C and all mixtures D obtained in step 1 to obtain mixed rubber E; Step 3: Evenly mix all the mixed rubber obtained in step 2 with catalyst A to obtain high-compression and oxidation-resistant silicone rubber.

[0026] In the above process, dodecafluoroheptyl methacrylate and methyltriallylsilane are subjected to a grafting reaction through the action of inhibitor and catalyst B, wherein the active group of allyl fluorinated benzene reacts with an active group in methyltriallylsilane to generate a graft containing an active group.

[0027] After white carbon black and fiber filler are evenly dispersed in active group double-terminated polydimethylsiloxane and 1,1,3,3,5,5-hexamethyltrisiloxane, they are added to methyl vinyl silicone rubber through reactant C. During the heating process, the raw material system is further reacted to form a mixed rubber, which is further reacted to produce a macromolecular cross-linked network structure under the action of a catalyst.

[0028] The particle size of white carbon is preferably 500 mesh.

[0029] In summary, this application has the following beneficial effects: 1. In the present application, the reactants formed by dodecafluoroheptyl methacrylate and methyl triallylsilane, active group double-terminated polydimethylsiloxane and 1,1,3,3,5,5-hexamethyltrisiloxane are compounded and cross-linked with methyl vinyl silicone rubber to form a multi-branched cross-linked network structure, and then combined with fiber filler and white carbon black, and with the assistance of a catalyst, the obtained silicone rubber has better mechanical properties, antioxidant corrosion properties and compressive properties.

[0030] 2. Through the action of inhibitor and catalyst B, dodecafluoroheptyl methacrylate and methyltriallylsilane are subjected to a grafting reaction, wherein the active group of allyl fluorinated benzene reacts with an active group in methyltriallylsilane to generate a graft containing an active group.

[0031] After white carbon black and fiber filler are evenly dispersed in active group double-terminated polydimethylsiloxane and 1,1,3,3,5,5-hexamethyltrisiloxane, they are added to methyl vinyl silicone rubber through reactant C. During the heating process, the raw material system is further reacted to form a mixed rubber, which is further reacted to produce a macromolecular cross-linked network structure under the action of a catalyst. DETAILED DESCRIPTION

[0032] The present application is further described in detail below with reference to the embodiments. Example

[0033] Example 1 A high-pressure-resistant and anti-oxidation-corrosion silicone rubber is prepared by the following method: Step 1: weigh 5 kg of dodecafluoroheptyl methacrylate, 3 kg of methyl triallylsilane, 0.03 kg of catalyst B, and 0.001 kg of inhibitor, put them into a reactor, mix them evenly, heat them to 60° C., and react them for 1 hour to obtain reactant C; weigh 1 kg of active group double-terminated polydimethylsiloxane, 20 kg of 1,1,3,3,5,5-hexamethyltrisiloxane, 10 kg of white carbon black, and 15 kg of fiber filler, and mix them evenly to obtain mixture D; Step 2: According to parts by weight, 100 kg of methyl vinyl silicone rubber, all reactants C obtained in step 1, and all mixtures D are weighed and mixed evenly to obtain a mixed rubber E; Step 3: All the mixed rubber obtained in step 2 is mixed evenly with 3 kg of catalyst A in a double-roll mixer to obtain a high-compression and oxidation-resistant silicone rubber.

[0034] The methyl vinyl silicone rubber has a vinyl content of 0.17% and a number average molecular weight of 100,000. Catalyst B is benzoyl peroxide; the inhibitor is p-hydroxyanisole. Catalyst A is a platinum catalyst. The fiber filler is polyetheretherketone fiber. The active group double-terminated polydimethylsiloxane is double-terminated methacryloyloxypropyl polydimethylsiloxane. The number average molecular weight of the active group double-terminated polydimethylsiloxane is 5000. The average wire diameter of the fiber filler is 2 microns and the length is 20 microns.

[0035] Example 2-3 The difference between Example 2-3 and Example 1 is that the amount of raw materials and process parameters are different, as shown in Table 1; Table 1 Raw material dosage of Examples 1-3 (kg) Example 4 The difference between Example 4 and Example 2 is that the methyl vinyl silicone rubber is obtained by mixing 20 kg of methyl vinyl silicone rubber with a vinyl content of 0.08%, 30 kg of methyl vinyl silicone rubber with a vinyl content of 0.30%, and 50 kg of methyl vinyl silicone rubber with a vinyl content of 1.27.

[0036] Example 5 The difference between Example 5 and Example 2 is that the methyl vinyl silicone rubber is obtained by mixing 30 kg of methyl vinyl silicone rubber with a vinyl content of 0.15%, 30 kg of methyl vinyl silicone rubber with a vinyl content of 0.25%, and 40 kg of methyl vinyl silicone rubber with a vinyl content of 1.01.

[0037] Example 6 The difference between Example 6 and Example 2 is that the methyl vinyl silicone rubber is obtained by mixing 40 kg of methyl vinyl silicone rubber with a vinyl content of 0.17%, 40 kg of methyl vinyl silicone rubber with a vinyl content of 0.18%, and 20 kg of methyl vinyl silicone rubber with a vinyl content of 1.15.

[0038] Example 7 The difference between Example 7 and Example 5 is that the active group-terminated polydimethylsiloxane is hydroxyl-diterminated polydimethylsiloxane.

[0039] Example 8 The difference between Example 8 and Example 5 is that the active group-terminated polydimethylsiloxane is aminopropyl di-terminated polydimethylsiloxane.

[0040] Example 9 The difference between Example 9 and Example 5 is that the active group double-terminated polydimethylsiloxane is composed of hydroxyl double-terminated polydimethylsiloxane, aminopropyl double-terminated polydimethylsiloxane, and double-terminated methacryloxypropyl polydimethylsiloxane in a weight ratio of 1:1.2:3.

[0041] Example 10 The difference between Example 10 and Example 5 is that the active group double-terminated polydimethylsiloxane is composed of hydroxyl double-terminated polydimethylsiloxane, aminopropyl double-terminated polydimethylsiloxane, and double-terminated methacryloxypropyl polydimethylsiloxane in a weight ratio of 1:1.5:2.

[0042] Embodiment 11 The difference between Example 11 and Example 5 is that the active group double-terminated polydimethylsiloxane is composed of hydroxyl double-terminated polydimethylsiloxane, aminopropyl double-terminated polydimethylsiloxane, and double-terminated methacryloxypropyl polydimethylsiloxane in a weight ratio of 1:1.8:1.

[0043] Example 12 The difference between Example 12 and Example 10 is that the fiber filler is aramid fiber.

[0044] Embodiment 13 The difference between Example 13 and Example 10 is that the fiber filler is composed of polyetheretherketone fiber and aramid fiber in a weight ratio of 1:1.5.

[0045] Embodiment 14 The difference between Example 14 and Example 13 is that both the white carbon black and the fiber filler are surface-treated, and the specific process is as follows: weigh γ-aminopropyltriethoxysilane, a 50% ethanol solution by mass, and white carbon black, stir at a speed of 100 r / min for 30 minutes, filter, and dry the filter residue at 80°C for 1 hour to obtain surface-treated white carbon black; wherein the weight ratio of γ-aminopropyltriethoxysilane, 50% ethanol solution by mass, and white carbon black is 1:5:10.

[0046] Weigh γ-aminopropyltriethoxysilane, 50% ethanol solution by mass, and fiber filler, stir at 100 r / min for 30 min, filter, and dry the filter residue at 80°C for 1 h to obtain a surface-treated fiber filler; wherein the weight ratio of γ-aminopropyltriethoxysilane, 50% ethanol solution by mass, and fiber filler is 1:5:10.

[0047] Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the active group di-terminated polydimethylsiloxane is replaced by an equal amount of 1,1,3,3,5,5-hexamethyltrisiloxane.

[0048] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that methyltriallylsilane is replaced by dodecafluoroheptyl methacrylate in an equal amount.

[0049] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that the active group double-terminated polydimethylsiloxane is replaced by methacryloyloxypropyl mono-terminated dimethylpolysiloxane in equal amounts.

[0050] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that the fiber filler is replaced by white carbon black in equal amount.

[0051] Performance testing Testing method / test method Mechanical properties: The high compression and oxidation resistance and corrosion resistance silicone rubber obtained in Examples 1-14 and Comparative Examples 1-4 was placed in a mold, and then placed in a flat vulcanizer, and vulcanized for 5 minutes at a temperature of 160°C to obtain a test sample, and the tensile strength and elongation at break of the test sample were tested with reference to ASTMD638; Compression resistance: Examples 1-14 and Comparative Examples 1-4 were placed in an extruder for extrusion molding. At a temperature of 160°C, cross-linking and shaping were performed for 5 minutes to obtain a test tube with an inner diameter of 20 mm and an outer diameter of 25 mm, and a compression test was performed. The pressure test was performed using a pneumatic device. The effective length of the test tube was 20 cm. One end of the test sample was sealed by a seal to prevent gas leakage. The other end was filled with nitrogen to make the inside of the test tube reach a certain pressure. The pressure was tested in turn at 3MPa, 4.0MPa, 5MPa, 6MPa, 7MPa, 8MPa, 9MPa, and 10MPa. Each test was maintained at a pressure of 5 minutes. If deformation, bursting, etc. occurred, the pressure of the corresponding deformation was recorded. If there was no change, the test pressure was increased, and the test was continued until deformation, bursting, etc. occurred, and the corresponding pressure was recorded.

[0052] Anti-oxidation corrosion: Place the test sample in an environment with a temperature of 250℃, a pressure of 30MPa, and a hydrogen volume concentration of 50% for 7 days, take it out and then test it according to the above-mentioned mechanical properties test method, and calculate the residual rate of tensile strength and the residual rate of elongation at break. The residual rate is equal to the data after aging divided by the data before aging.

[0053] The above experiment was carried out 3 times and the average value was taken. The specific experimental data are shown in Table 2; Table 2 Experimental data of Examples 1-14 and Comparative Examples 1-4 By comparing Example 1 with Comparative Examples 1-6, it can be seen that the elongation at break, tensile strength, compressive pressure, residual elongation at break, and residual tensile strength of Comparative Examples 1-6 are all lower than those of Example 1, indicating that the silicone rubber prepared by adopting the raw material system of the present application has better oxidation corrosion resistance, compressive resistance, and mechanical properties, reducing the possibility of cracking in hydrogen energy vehicles and improving its practicality.

[0054] By comparing Example 2 and Example 4, it can be seen that the elongation at break, tensile strength, compressive pressure, residual elongation at break and residual tensile strength of Example 4 are all higher than those of Example 2, indicating that the compounding of methyl vinyl silicone rubber with a vinyl content of 0.08-0.17%, methyl vinyl silicone rubber with a vinyl content of 0.18-0.30% and methyl vinyl silicone rubber with a vinyl content of 1.01-1.27 has better corrosion resistance and mechanical properties.

[0055] By comparing Example 5 and Example 10, it can be seen that the elongation at break, tensile strength, compressive pressure, residual elongation at break and residual tensile strength of Example 10 are all higher than those of Example 5, indicating that the use of hydroxyalkyl double-terminated polydimethylsiloxane, aminopropyl double-terminated polydimethylsiloxane and double-terminated methacryloxypropyl polydimethylsiloxane has a synergistic effect, thereby enabling the silicone rubber to obtain better performance.

[0056] By comparing Example 13 with Example 10, it can be seen that the elongation at break, tensile strength, compressive pressure, residual elongation at break and residual tensile strength of Example 13 are all higher than those of Example 10, indicating that the compounding of polyetheretherketone fiber and aramid fiber has a better synergistic effect, thereby making the performance of silicone rubber better.

[0057] By comparing Example 13 and Example 14, it can be seen that the elongation at break, tensile strength, compressive pressure, residual elongation at break and residual tensile strength of Example 13 are all lower than those of Example 14, indicating that after the surface treatment of the present application, the surface treated silica and surface treated fiber filler obtained have better compatibility, further improving the physical properties of the silicone rubber.

[0058] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A high compression and oxidation corrosion resistant silicone rubber, characterized in that: It is composed of the following raw materials in parts by weight: 100 parts of methyl vinyl silicone rubber Active group double-terminated polydimethylsiloxane 1-8 parts 1,1,3,3,5,5-Hexamethyltrisiloxane 10-20 parts 1-5 parts of dodecafluoroheptyl methacrylate 3-5 parts of methyl triallylsilane 10-30 parts of white carbon black Fiber filler 5-15 parts Catalyst A1-3 parts Catalyst B 0.01-0.03 parts Inhibitor 0.001-0.003 parts.

2. The high pressure resistance and oxidation resistance silicone rubber according to claim 1, characterized in that: The methyl vinyl silicone rubber is composed of the following raw materials in parts by weight: 20-40 parts of methyl vinyl silicone rubber with a vinyl content of 0.08-0.17% 30-40 parts of methyl vinyl silicone rubber with a vinyl content of 0.18-0.30% 20-50 parts of methyl vinyl silicone rubber with a vinyl content of 1.01-1.

27.

3. The high pressure resistance and oxidation resistance silicone rubber according to claim 1, characterized in that: The number average molecular weight of the methyl vinyl silicone rubber is 100,000-500,000.

4. The high pressure resistance and oxidation corrosion resistance silicone rubber according to claim 1, characterized in that: The number average molecular weight of the active group double-terminated polydimethylsiloxane is 5000-8000.

5. The high compression and oxidation-resistant silicone rubber according to claim 1, characterized in that: The active group double-terminated polydimethylsiloxane is one or more of hydroxyl double-terminated polydimethylsiloxane, aminopropyl double-terminated polydimethylsiloxane and double-terminated methacryloxypropyl polydimethylsiloxane.

6. The high pressure resistance and oxidation corrosion resistance silicone rubber according to claim 5, characterized in that: The active group double-terminated polydimethylsiloxane is composed of hydroxyl double-terminated polydimethylsiloxane, aminopropyl double-terminated polydimethylsiloxane and double-terminated methacryloxypropyl polydimethylsiloxane in a weight ratio of 1: (1.2-1.8): (1-3).

7. The high compression and oxidation-resistant silicone rubber according to claim 1, characterized in that: The fiber filler is polyetheretherketone fiber and / or aramid fiber.

8. The high pressure resistance and oxidation corrosion resistance silicone rubber according to claim 1, characterized in that: The catalyst A is a platinum catalyst or a dipentadienyl vulcanizing agent.

9. The high compression and oxidation corrosion resistant silicone rubber according to any one of claim 1, characterized in that: The catalyst B is benzoyl peroxide; the inhibitor is p-hydroxyanisole.

10. A method for preparing the high compression and oxidation corrosion resistant silicone rubber according to any one of claims 1 to 9, characterized in that: The following steps are involved: Step 1: weigh dodecafluoroheptyl methacrylate, methyl triallylsilane, inhibitor, and catalyst B in parts by weight, mix them evenly, and heat them for reaction to obtain reactant C; mix active group double-terminated polydimethylsiloxane, 1,1,3,3,5,5-hexamethyltrisiloxane, white carbon black, and fiber filler in parts by weight to obtain mixture D; Step 2: Weigh methyl vinyl silicone rubber in parts by weight, and evenly mix all reactants C and all mixtures D obtained in step 1 to obtain mixed rubber E; Step 3: Evenly mix all the mixed rubber obtained in step 2 with catalyst A to obtain high-compression and oxidation-resistant silicone rubber.

Citation Information

Patent Citations

  • Motor slot wedge high-temperature-resistance insulation material

    CN105238062A

  • High-resilience silicone rubber and preparation method thereof

    CN109467939A

  • High-tear-resistance white carbon black / methyl vinyl silicone rubber composite material and preparation method thereof

    CN113527888A

  • Curable composition for sealing material

    JP2005194420A

  • Antistructure agent

    US3956166A